The affective atmospheres of democratic education: pedagogical and political implications for challenging right-wing populism. Issue 4 (4th July 2022) - Zembylas, Michalinos
ABSTRACT: This paper draws on the concept of affective atmospheres to theorize how democracy and democratic education take hold and circulate in classrooms and schools. The paper asks under which circumstances affective atmospheres are experienced or even 'engineered', encompassing affective and material features that (de)legitimate democracy, democratic education and right-wing populism. The aim is to render the concept of atmosphere tractable through a line of theorizing that recognizes the affective force of democracy and right-wing populism and asks how democratic education may respond by paying careful attention to democracy as affectively produced and transmitted. The paper also examines what it would take to reinvigorate the affective atmospheres of democratic education in schools in light of the rise of right-wing populist affectivity. The analysis makes a contribution to the challenge of asking how right-wing populist affectivity might be resisted in the context of democratic education.